PENGARUH FAKTOR GEOGRAFIS TERHADAP HARGA KEBUTUHAN POKOK DI PASAR TRADITIONAL - Francisca Hermawan; Clara Herlina Karjo; Bertha Napitupulu (Universitas Ahmad Dahlan, 2019)
The affordable price of staple materials (basic food) is one of the conditions in order for the wheels of the economy run smoothly on food can meet the needs of the community. However, the price of basic commodities in traditional markets is not always same each others, its depends on the location of the markets. This research was conducted by census in five traditional market in Jakarta to figure out the difference in the price of staple based on the location of its markets. The data used in the form of prices of 10 types of staple in every market. Data analysis was performed with statistical program as known as SPSS version 22 by using Analysis of Variance (ANOVA). The results showed that the price of the staple in the market is stable and not very influential on the ability of purchasing power despite the location investigated is different. Expected from this research, the society remained traditional market shopping.